Oxidarea catalitică cu apă oxigenată a colorantului portocaliu activ din soluţiile model [Articol] - Duca, Gheorghe; Matveevici, Vera; Gonța, Maria; Iambarțev, Viorica (CEP USM, 2008)
The processes of catalytic oxidation of textile colorant orange active (PA) wizh hydrogen peroxide were studied, indepemdence on the concentration of hydrogen peroxide, iron (II), initial concentration of colorant, with and withoutsubsequent boiling of model solutions. It was found that the effect of de-coloration and mineralization degree of colorant PA depends on concentration ofhydrogen peroxide and colorant. Maximal mineralization reached was 84-85%. In case of subsequent boiling of modelsolutions, following their catalitic oxidation, mineralization degree was increased reaching up to 97-98% in 5 minutes time
Keywords: oxidarea catalitică; colorantul PA